COVID-19 Vaccination Uptake and Self-Reported Side Effects among Healthcare Workers in Mbale City Eastern Uganda - Madut Akech, Gabriel; Kanyike, Andrew Marvin; Galabuzi Nassozi, Ashah; Aguti, Beatrice; Nakawuki, Ashley Winfred; Kimbugwe, Denis; Kiggundu, Josen; Maiteki, Robert; Mukyala, Dorothy; Bongomin, Felix; Obakiro, Samuel Baker; Nekaka, Rebecca; et al. (medRxiv, 2022)
Fear of anticipated side effects has hindered the COVID-19 vaccination program globally. We report the uptake and the self-reported side effects (SEs) of the COVID-19 vaccine among Healthcare workers (HCWs) in Mbale City Eastern Uganda. Methods: A cross-sectional survey of HCWs at seven different level health facilities was conducted from 6th September to 7th October 2021 using a structured self-administered questionnaire. Results: COVID-19 vaccine had been received by 119 (69%) participants of which 79 (66%) received the two recommended doses of the AstraZeneca vaccine. Getting vaccinated was associated with working in a lower health facility (aOR= 14.1, 95% CI: 4.9 – 39.6, P=0.000), perceived minor risk of contracting COVID-19 (aOR= 12.3, 95% CI: 1.0 – 44.6, p=0.047), and agreeing that COVID-19 vaccine is protective (aOR= 16.7, 95% CI: 5.6 – 50.4, p=0.000). 97 (82%) of participants experienced side effects to at least one dose of which most were mild on both the first (n=362, 51%) and second dose (n=135, 69%). The most frequently reported side effects on the first and second dose were fever (79% and 20%), injection site pain (71% and 25%), and Fatigue (69% and 20%) respectively. Conclusions: The majority of the HCWs in Mbale City had received at least one dose of the COVID-19 vaccine and experienced a side effect. The side effects were mostly mild on either dose thus the vaccines are generally safe.
Keywords: COVID-19 vaccine; Associated factors; Side effects; Healthcare workers; Eastern Uganda